2015
DOI: 10.15376/biores.11.1.296-305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Relative Humidity and Temperature on Photodegradation Processes in Beech and Spruce Wood

Abstract: Spruce and beech samples were irradiated by UV light in humid (100% air humidity) and dry conditions to clarify the effects of vapor on photodegradation. UV-irradiated samples were also soaked in distilled water for comparison. The color change and the IR absorption spectra were measured. The wet condition generated considerably greater discoloration than did the dry condition. The intensity of the color change was higher at elevated temperature (53 °C) than at 32 °C. The results showed that the presence of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Fourier transform infrared spectroscopy (FT-IR) is a fast, simple and sensitive method for the structural characterisation of many different materials, including wood. It has already been used for qualitative and quantitative evaluation of main wood components [23] or to study chemical and structural changes in wood polymers during biodegradation and weathering [24][25][26]. As the method requires only a small amount of the studied material, the technique proved to be useful for research on historical wooden objects.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy (FT-IR) is a fast, simple and sensitive method for the structural characterisation of many different materials, including wood. It has already been used for qualitative and quantitative evaluation of main wood components [23] or to study chemical and structural changes in wood polymers during biodegradation and weathering [24][25][26]. As the method requires only a small amount of the studied material, the technique proved to be useful for research on historical wooden objects.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, extractives are of great importance in wood technology; they can affect the successful implantation of hydrothermal wood processing (e.g., wood drying), which is necessary in the production of finished wood products. It has been suggested that extractives, especially polyphenols among others, participate in the colour changes of wood during tree growth (Vek et al 2014(Vek et al , 2015 or wood processing (Burtin et al 1998;Kreber et al 1998;Pervan et al 2006;Esteves et al 2008;Straže et al 2008;SandovalTorres et al 2010;Chen et al 2014;Tolvaj et al 2016). Sundqvist and Morén (2002) concluded that the degradation products of wood polymers and extractives participate in wood colour formation during hydrothermal processing.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the above results ( Figure 4 , Figure 5 , Figure 6 and Figure 7 ) and the test methodology used, the effect of colour changes tends to be emphasized by the higher moisture of the underlying wood species and higher temperature [ 83 ]. Adversely, prolonged test times do not lead to significantly higher colour changes in wood compared to the initial stages of photodegradation [ 5 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%